Efeitos do treinamento físico aeróbio ou resistido em parâmetros autonômicos e de estresse oxidativo em ratas hipertensas ooforectomizadas - Palma, Renata Kelly da (2012)
The purpose of the present study was to investigate the effects of or resistance or aerobic exercise on cardiovascular autonomic control and oxidative stress in ovariectomized hypertensive rats. Female spontaneously hypertensive rats (SHR) were divided into 4 groups (n=8 each): sedentary (HS), sedentary ovariectomized (HSO), aerobic trained ovariectomized (HATO) and resistance trained ovoriectomized (HRTO). The aerobic training (AT) was performed on a treadmill and the resistance exercise training (RT) was performed on a vertical ladder with weights attached to rat tail (5days/week,8 weeks). Arterial pressure (AP) and heart rate (HR) were directly recorded; baroreflex sensitivity (BRS) was evaluated by bradycardic (BR) and tachycardic responses (TR) and autonomic modulation was evaluated by time-domain and frequency-domain. Oxidative stress was evaluated in cardiac tissue by lipid peroxidation,protein oxidation, the ratio glutathione reductase/glutathione oxidized (GSSG/GSH) and catalase (CAT), superoxide dismutase (SOD) and glutathione peroxidase (GPx) antioxidant enzyme activities. Theovariectomy induced increase in BP, TR reduction, increased vascular sympathetic modulation,cardiac sympatho-vagal balance and lipid peroxidation. The exercise training induced a reduction in BP (HATO:146±3,1 e HRTO: 159±2,2 vs. HS:168±3,4 e HSO:177±3,4 mmHg) and bradycardia (HATO: 331±6.4 and HRTO: 332±9 vs. HS: 363±7 and HSO: 356±5.1 bpm) in HATO and HRTO groups in compared to sedentarygroups. AT increased TR in relation to other groups.However, BR was better for both HATO and HRTO in relation to HS and HSOgroups. Both exercise trainings attenuated the increased vascular sympathetic modulation and AT improved parasympathetic modulation and spontaneously BRS (α index).Lipid peroxidation was reduced in trained groups in relation to sedentary groups (HRTO: 3649±168 and HATO: 4202±310 vs. HSO: 6514±547 and HS: 6661±566 cps/mg protein). The protein carbonylation reduced in trained groups as well. The ratio GSSG/GSH did not differ between groups, however GSSG was higher in HATO group as compared to other groups and GSH was lower in HRTO group as compared to HATO. CAT was higher in trained groups in compared to HS.SOD activity increased in HATO and HRTO in relation to sedentary groups. Additional enhancement was observed: for CAT in HATO group and for SOD in HRTO group. GPx activity was higher in HRTO in relation to HSO. Moreover, lipid peroxidation and protein carbonylation showed a correlations with VARPAS and RMSSD. In conclusion, resistance or aerobic exercise training induced a reduction in AP and HRrelated to attenuation of autonomic dysfunction in SHR ovariectomized rats. These changes were probably related to autonomic-induced improvement in cardiac oxidative stress profile.